Clinical significance of gastrointestinal bleeding after living donor liver transplantation. (10th May 2014) - Kimura, Koichi; Ikegami, Toru; Bekki, Yuki; Ninomiya, Mizuki; Yamashita, Yo‐ichi; Yoshizumi, Tomoharu; Yoshiya, Shohei; Soejima, Yuji; Harada, Noboru; Shirabe, Ken; Maehara, Yoshihiko
Summary The clinical presentations of gastrointestinal bleeding (GIB) occurring after living donor liver transplantation (LDLT) have not been fully described. We performed a retrospective analysis of 297 LDLT cases. Nineteen patients (6.4%) experienced GIB after LDLT. The etiology of GIB included bleeding at the jejunojejunostomy following hepaticojejunostomy (n = 13), peptic ulcer disease (n = 2), portal hypertensive gastropathy (n = 2), and other causes (n = 2). Hemostasis was achieved in 13 patients (68.4%) by endoscopic (n = 3), surgical (n = 1), or supportive treatments (n = 15), but not in the other six patients. Graft dysfunction (P < 0.001), hepaticojejunostomy (P = 0.01), portal vein pressure at the end of surgery >20 mmHg (P = 0.002), and operative blood loss >10 L (P = 0.004) were risk factors. One‐year graft survival rate was significantly lower in patients with GIB than in patients without GIB (P < 0.001). The inhospital mortality rate was 52.6% for patients with GIB, 75.0% for patients with graft dysfunction, and 14.3% for patients without graft dysfunction (P = 0.028). Despite its infrequency after LDLT, GIB has strong correlation with graft dysfunction and inhospital mortality.